The combinatorial innexin code of heterochannel electrical synapses governs synaptic function and is maintained by distinct cellular mechanisms - Atal Vats; Muraleedharan Sudhanand; Ananya Bandyopadhyay; Marlyn Xavier Mascarenhas; Nayantara Varma; Sandhya Padmanabhan Koushika; Abhishek Bhattacharya (Proceedings of the National Academy of Sciences, 2026)
Diversity in the molecular composition of intercellular gap junction channels, the functional units of electrical synapses, determines their physiological properties. Yet the mechanisms by which neurons coordinate the use of multiple coexpressed gap junction proteins—connexins or innexins—to establish selective connections with distinct synaptic partners remain largely unknown. Using the posterior mechanosensory circuit in Caenorhabditis elegans, we found that individual electrical synapses can form by clustering molecularly distinct gap junction channel types composed of three different innexin proteins: INX-1, UNC-7, and UNC-9. This previously uncharacterized combinatorial configuration, which we term heterochannel synapses, enables molecularly distinct gap junction channel types to collaborate functionally to regulate posterior touch sensory behavior and enhance functional robustness. We show that the synaptic trafficking of these molecularly distinct channel types within a heterochannel synapse is independently regulated by specific and conserved kinesin motor proteins, while distinct molecular pathways involving channel type-specific retrograde kinesins control their turnover. These independent, channel-specific regulatory mechanisms allow for individual synapse-level alterations in the combinatorial innexin code of heterochannel synapses in response to altered environmental conditions, providing a mechanism for electrical synapse plasticity. Finally, we present evidence and functional significance of heterochannel electrical synapses in C. elegans locomotory circuits. Altogether, our findings demonstrate a combinatorial heterochannel organization of electrical synapses, their functional significance, and the regulatory mechanisms that govern them.